2019
DOI: 10.48550/arxiv.1909.10928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimagic orientations of graphs with given independence number

Abstract: Given a digraph D with m arcs and a bijection τ : A(D) → {1, 2, . . . , m}, we say (D, τ ) is an antimagic orientation of a graph G if D is an orientation of G and no two vertices in D have the same vertex-sum under τ , where the vertex-sum of a vertex u in D under τ is the sum of labels of all arcs entering u minus the sum of labels of all arcs leaving u. Hefetz, Mütze, and Schwartz in 2010 initiated the study of antimagic orientations of graphs, and conjectured that every connected graph admits an antimagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Particulary, they showed that every orientation of stars (other than K 1,2 ), wheels, and complete graphs (other than K 3 ) is antimagic. Conjecture 2 has been also verified for regular graphs [9,12,14,16], biregular bipartite graphs with minimum degree at least two [13], Halin graphs [19], graphs with large maximum degree [17], and graphs with large independence number [15]. In this paper, by supporting Conjecture 2, we obtain the results below.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Particulary, they showed that every orientation of stars (other than K 1,2 ), wheels, and complete graphs (other than K 3 ) is antimagic. Conjecture 2 has been also verified for regular graphs [9,12,14,16], biregular bipartite graphs with minimum degree at least two [13], Halin graphs [19], graphs with large maximum degree [17], and graphs with large independence number [15]. In this paper, by supporting Conjecture 2, we obtain the results below.…”
Section: Introductionsupporting
confidence: 73%
“…The following result was proved in [15] without the furthermore part. However, the furthermore part is easy to obtain by following the same proof of Lemma 2.2 in [15] by just letting vertices in T to be not the endvertices of the edge-disjoint trails that decompose E(G), which can be definitely guaranteed by the conditions imposed on T . So we omit the proof.…”
Section: Notation and Preliminary Lemmasmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the Euler circuit, one can estimate the vertex sum of each vertex induced by the circuit. Our first lemma below is almost the same as Lemma 2.1 in [9], Lemma 2.2 in [19], and Lemma 7 in [14]. For the sake of completeness, we present the proof in the note.…”
Section: Resultsmentioning
confidence: 95%
“…There are several families of graphs proved to satisfy Conjecture 1.2 by different groups of researchers: K n with n ≥ 4, S n with n ≥ 3, W n with n ≥ 3, the (2d + 1)-regular graphs with d ≥ 0 by Hefetz et al [5]; the 2d-regular graphs with d ≥ 2 by Li, Song, Wang, Yang, and Zhang [9], by Yang [22], and by Song and Hao [18]; the biregular graphs by Shan and Yu [15]; the Halin graphs by Yu, Chang, and Zhou [24]; the caterpillars by Lozano [11]; the lobsters by Gao and Shan [7]; and the complete k-ary trees by Song and Hao [17]. In addition to the above special graphs, Yang, Carson, Owens, Perry, Singgih, Song, Zhang, and Xhang [23], proved that every connected graph with at least n ≥ 9 vertices and maximum degree at least n − 5 admits an antimagic labeling, and Song, Yang, and Zhang [19] proved that every graph G with independent number at most 4 or least |V (G)|/2 admits an antimagic orientation. Some of the above results are also true for disconnected graphs.…”
Section: Introductionmentioning
confidence: 99%